The Role of Educational Policy in Mitigating Cyberbullying and Its Impact on Students’ Cognitive Development - Kadi Sukarna; Ika Nurwulandari; Zainal Arifin (Newinera Publisher, 2026)
The rapid development of information and communication technology has significantly transformed students’ social interactions, particularly through digital platforms, which has also increased the risk of cyberbullying. This study aims to examine the role of educational policy in mitigating cyberbullying and its impact on students’ cognitive development. A quantitative approach with an ex post facto design was employed, involving elementary school students as research participants. Data were collected using Likert-scale questionnaires measuring educational policy implementation, cyberbullying experiences, and cognitive development, and were analyzed using descriptive statistics, multiple regression, and path analysis.The findings indicate that educational policy has a significant negative effect on cyberbullying, suggesting that better policy implementation contributes to reducing cyberbullying incidents. Furthermore, cyberbullying has a significant negative impact on students’ cognitive development, particularly in terms of concentration, critical thinking, and problem-solving abilities. The mediation analysis reveals that cyberbullying acts as an intervening variable in the relationship between educational policy and cognitive development. This means that educational policy not only has a direct influence on cognitive outcomes but also indirectly affects them through the reduction of cyberbullying.These results highlight the importance of strengthening educational policies that integrate digital literacy, character education, and preventive strategies to create a safe learning environment. Effective policy implementation can minimize the negative impact of cyberbullying and support optimal cognitive development among students. This study contributes to the existing literature by providing empirical evidence on the interconnected relationship between educational policy, cyberbullying, and cognitive development in the context of digital education.